SEARCH AND RESCUE SYSTEM IN POLAND - Jan RAJCHEL (Scientific Journal of Silesian University of Technology. Series Transport)
On the 25th of January 2018, the Civil and Military Aeronautical Rescue Coordination Centre (ARCC) commenced operations in the Polish Air Navigation Services Agency (PANSA). PANSA significantly increased its contribution in the domain of coordination of search and rescue activities in ASAR service in the Polish area of responsibility. Before this date, all tasks of ARCC Centre were conducted mainly by the Armed Forces of the Republic of Poland, which performed the coordination function in ASAR (Aeronautical Search and Rescue) service. The bodies responsible were the Aeronautical Search and Rescue Centre located in the Air Operations Centre – Air Component Headquarter in Warsaw and the sub-centre in Gdynia, part of the Naval Operations Centre of Naval Component Headquarter. According to international commitments resulting mainly from the Convention on International Civil Aviation signed on 7th of December 1944 in Chicago and ratified by Poland together with Annex 12 “Search And Rescue”, Poland committed to establishing aeronautical search and rescue service called ASAR within the Polish region to assure its operation. ASAR service is the only service in Poland for rescue purposes and is designated for the search and rescue of aircraft in distress, provision of help for aircraft crews and passengers and other victims of aeronautical accidents (regardless of the nationality of the aircraft and persons). ASAR service tasks include search of the designated area to locate aircraft and victims of aeronautical accidents, determine their status and commence rescue actions at the location using dedicated forces and measures as well as forces and measures of other systems, mainly from the State Medical Rescue and the National Firefighting and Rescue System and the Maritime Search and Rescue Service. ASAR services consists of: commanding element – CivilMilitary Aeronautical Rescue and Coordination Centre, executive elements – Aeronautical Search and Rescue Teams (LZPR), and supporting elements – alerting points (air traffic services units operating in the framework of alerting service).